2009
DOI: 10.1090/s0002-9939-09-09875-x
|View full text |Cite
|
Sign up to set email alerts
|

On the $L_p$ norm of the Rademacher projection and related inequalities

Abstract: Abstract. The purpose of this paper is to find the exact norm of the Rademacher projection onto {r 1 , r 2 , r 3 }. Namely, we prove

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
2
1
0
Order By: Relevance
“…This result was obtained originally in [34] for n = 2, 3, 4.) G. Lewicki and L. Skrzypek showed that c p in (11) tends to c p in (6) as n → ∞ and recovered C. Franchetti's result.…”
Section: Introduction: Estimates For Centred Momentssupporting
confidence: 76%
“…This result was obtained originally in [34] for n = 2, 3, 4.) G. Lewicki and L. Skrzypek showed that c p in (11) tends to c p in (6) as n → ∞ and recovered C. Franchetti's result.…”
Section: Introduction: Estimates For Centred Momentssupporting
confidence: 76%
“…(If n=3,4$n = 3, 4$, then the inequality kn<12$\frac{k}{n} &lt; \frac{1}{2}$ means that k=1$k = 1$, and (1.11) takes the form cpbadbreak=false(n1false)p1+11pfalse(n1false)1p1+111pn0.16em.$$\begin{equation*} c_p = \frac{ {\left((n - 1)^{p - 1} + 1\right)}^{\frac{1}{p}} {\left((n - 1)^{\frac{1}{p - 1}} + 1\right)}^{1 - \frac{1}{p}}}{n}\, . \end{equation*}$$This result was obtained originally in [34] for n=2,3,4$n = 2, 3, 4$.) G. Lewicki and L. Skrzypek showed that cp$c_p$ in (1.11) tends to cp$c_p$ in (1.6) as n$n \rightarrow \infty$ and recovered C. Franchetti's result.…”
Section: Introduction: Estimates For Centered Momentssupporting
confidence: 69%
“…(see (1.7)), where This result was obtained originally in [34] for 𝑛 = 2, 3, 4.) G. Lewicki and L. Skrzypek showed that 𝑐 𝑝 in (1.11) tends to 𝑐 𝑝 in (1.6) as 𝑛 → ∞ and recovered C. Franchetti's result.…”
Section: Introduction: Estimates For Centered Momentsmentioning
confidence: 55%